Anion-induced AgI self-assemblies with electron deficient aromatic ligands: anion–π-system interactions as a driving force for templated coordination networks1. Issue 46 (11th June 2015) - Safin, Damir A.; Pialat, Amélie; Leitch, Alicea A.; Tumanov, Nikolay A.; Korobkov, Ilia; Filinchuk, Yaroslav; Brusso, Jaclyn L.; Murugesu, Muralee
<x xml:space="preserve">Abstract</x> 1D, 2D and 3D AgI coordination polymers were isolated using nitrogen based 3, 6-bis(2′-pyrimidyl)-1, 2, 4, 5-tetrazine and 2, 4, 6-tris(2-pyrimidyl)-1, 3, 5-triazine ligands.